Tunable microwave photonic frequencies generation based on stimulated Brillouin scattering operating in the L-band region - Zulkifli, Mohd Zamani; Norizan, Siti Fatimah; Awang, Noor Azura; Zulkifli, Mohd Zamani (Wiley-Blackwell, 2011)
: A tunable up frequencies of microwave photonics based on stimulated Brillouin scattering (SBS) for application in radio over fiber is demonstrated. The experimental setup consists of 7.7 km dispersion compensated fiber, which acts as the nonlinear medium for generating the SBS and is pumped by a narrow linewidth (0.015 nm) tunable laser operating in L-band region. The input-modulated RF at 2 GHz is upshifted to new frequencies of 7.71, 7.68, 7.65, 7.62, 7.58, and 7.56 GHz at Brillouin pump wavelengths of 1580, 1585, 1590, 1595, 1600, and 1605 nm, respectively. This system allows certain tunability in the upshifted frequencies by using a tunable laser source. VC 2011 Wiley Periodicals, Inc. Microwave Opt Technol Lett 53:1710–1713, 2011; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.26106